2011
DOI: 10.1136/jnis.2010.004358
|View full text |Cite
|
Sign up to set email alerts
|

The role of circle of Willis anomalies in cerebral aneurysm rupture

Abstract: This series shows that circle of Willis anomalies are more commonly found in ruptured as opposed to unruptured cerebral aneurysms of the anterior and posterior communicating arteries. The presence of a circle of Willis anomaly may be an important characteristic for selecting patients for preventive aneurysm treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
(27 reference statements)
2
47
1
1
Order By: Relevance
“…Numerous studies suggest a role for hormones in aneurysm pathogenesis via its effect on vascular remodeling and have shown the benefits of hormone replacement therapy (HRT) on reducing aneurysm formation and rupture (Stober et al, 1985; Mhurchu et al, 2001; Stirone et al, 2003; Harrod et al, 2006; Lazzaro et al, 2012). The increase in female prevalence of cerebral aneurysms and SAH peaks between 50 and 59 years of age, in correlation with the fall in estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest a role for hormones in aneurysm pathogenesis via its effect on vascular remodeling and have shown the benefits of hormone replacement therapy (HRT) on reducing aneurysm formation and rupture (Stober et al, 1985; Mhurchu et al, 2001; Stirone et al, 2003; Harrod et al, 2006; Lazzaro et al, 2012). The increase in female prevalence of cerebral aneurysms and SAH peaks between 50 and 59 years of age, in correlation with the fall in estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the configuration of the circle of Willis was not strongly correlated to rupture, but that moderate risk could not be excluded. A more recent study showed that anomalies of the circle of Willis were more frequently found in ruptured than in unruptured aneurysms of the ACOM or PCOM arteries 75 . Thus, the authors speculate that increased flow in combination with vascular configurations that do not minimize the energy expenditure at bifurcations may, via turbulent flows and increased WSS, contribute to intracranial aneurysm formation and progression.…”
Section: Locationmentioning
confidence: 98%
“…Any variations in it may cause a disturbance in its flow [3]. The variations of the anterior circulation of the brain may lead to some clinical conditions like Cerebrovascular diseases such as stroke, aneurysms, internal carotid artery occlusion, unilateral flow restrictive external carotid artery disease, and migraine [8][9][10]. In mentally challenged patients, a higher percentage of anomalies of the circle of Willis was also reported [11].…”
Section: Study On the Anatomical Variations Of The Anterior Part Of Tmentioning
confidence: 98%